2020
DOI: 10.1080/13504622.2020.1752626
|View full text |Cite
|
Sign up to set email alerts
|

The political dimension of consuming animal products in education: An analysis of upper-secondary student responses when school lunch turns green and vegan

Abstract: Addressing the consumption of animals as an educative and environmentally crucial question, this paper empirically examines the meaning of meat and animal consumption for learners in school settings. This study is based on focus groups with Swedish upper secondary students and is centred around their responses to a vegan month at their school as an initiative to emphasise the environmental consequences caused by human consumption of animal products. In order to make sense of the students responses in light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Similarly, supporting Rothgerber (2020), greater conservatism correlates with greater 4N endorsement, anti-veg*nism and meat consumption willing ness, and lower animal empathy and meat distress (Earle et al, 2019). Veg*nism itself is also politicised as left-wing and 'politically correct', whilst meat consumption is deemed right-wing (Lindgren, 2020). Yet, contradicting these articles, Feinberg et al (2019) found no relationship between political ideology and moralization.…”
Section: Political Ideologymentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, supporting Rothgerber (2020), greater conservatism correlates with greater 4N endorsement, anti-veg*nism and meat consumption willing ness, and lower animal empathy and meat distress (Earle et al, 2019). Veg*nism itself is also politicised as left-wing and 'politically correct', whilst meat consumption is deemed right-wing (Lindgren, 2020). Yet, contradicting these articles, Feinberg et al (2019) found no relationship between political ideology and moralization.…”
Section: Political Ideologymentioning
confidence: 80%
“…These deliberately opposing responses reinstate a sense of personal choice (Brehm, 1966). Three articles within this review (Dowsett et al, 2018;Feinberg et al, 2019;Lindgren, 2020) evidence meat-related psychological reactance. For example, after watching videos on animal suffering in meat production, 'decreasers' demonstrate reduced meat consumption moralization over time and are less likely to reduce meat consumption than 'slight changers' or 'moralizers' (Feinberg et al, 2019).…”
Section: Dietmentioning
confidence: 99%
“…Two of the factors contributing to the harmful effects of this modus operandi are meat production, especially red meat, and food waste, which are responsible, among other factors, for a significant emission of greenhouse gases into the environment and/or consumption of freshwater [ 23 , 106 , 110 , 111 ]. Therefore, some practices related to the offer of vegetarian/vegan menus, with a reduction in the meat offering, the adequacy of the portion sizes, or the adoption of the single-course scholar menu have been reported in the literature [ 8 , 25 , 26 , 27 , 35 , 112 ]. Some instruments have been proposed to allow the planning of more environmentally sustainable menus based on reducing carbon and/or water footprints while addressing nutritional, economic, and cultural dimensions [ 7 , 113 , 114 , 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, meat consumption has been justified by harmlessness (the more meat is consumed, the perception of environmental disadvantages decreases [ 68 , 69 ], purposefulness (the belief in the rationality of one’s preferences [ 68 , 70 ], culture (typical of a given social group), and economy (meat sales revenues [ 68 , 70 ]. According to Western culture, a meat diet is viewed as typically male, while vegan and vegetarian diets as more female [ 71 , 72 ]. Eating meat may also be a way of expressing social identity, e.g., prestige or style [ 73 , 74 ] which has also been present throughout history, namely the rationality of consumption, fear of fat, vegetarian philosophy, or loss of trust.…”
Section: Discussionmentioning
confidence: 99%